Tindak Tutur Direktif Guru Bahasa Indonesia Kelas VII BSMP Muhammadiyah 10 Surakarta Dalam ProsesPembelajaran - Ardiawanto, Handoko Agus; , Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
The purpose of this research there are two The aims of this research are (1) to analyze the forms of directive utterance used by the teacher in teaching learning process at the class of VII B in SMP Muhammadiyah 10 Surakarta. (2) To analyze the strategies of directive utterance used by the teacher in teaching learning process at the class of VII B in SMP Muhammadiyah 10 Surakarta. This research uses descriptive qualitative method. The data source of this research is the oral utterance made by the teacher and the students of SMP Muhammadiyah 10 Surakarta in teaching learning process. The researcher uses observing technique, recording technique, and noting technique to collect the data. The data validity in this research is triangulation. The technique to analyze the data is extralingual equalization. The results of this research are (1) the researcher found 12 directive utterances in teaching learning process in SMP Muhammadiyah 10 Surakarta. The forms of directive utterance used by the teacher are commanding, ordering, giving suggestion, reminding, admonishing, threatening, forbidding, advising, requiring, insisting, inviting, and targeting. The dominant utterances used by the teacher are commanding, ordering, giving suggestion, reminding, and admonishing. (2) The directive utterance strategies used in teaching learning process are strategy of direct directive utterance and indirect directive utterance. The researcher found 14 data of direct directive utterance in this research. In the other hand, the strategy of indirect directive utterance divided into two types. The first strategy of indirect directive utterance is statement sentence mood. The second strategy of indirect directive utterance is interrogative sentence mood. J